Obesity and Its Various Etiologies (Revista de Medicina Clinica, 2024)
Obesity is a public health problem worldwide; the World Health Organization defines obesity as an abnormal or excessive accumulation of fat in adipose tissue that is detrimental to health associated with an increased risk of metabolic diseases. This disease is the consequence of a complex interaction between genetic, environmental and psychological factors. Now we know much better some of the genetic factors that influence obesity and the endocrine and metabolic alterations that it produces, however, it is clear that the obesity epidemic today has multiple etiologies. Environmental factors play a fundamental role in obesity, especially the decrease in physical activity due to technological advances and the transition towards diets rich in saturated fats and sugars.
Keywords: Obesity; Etiology; Environment